Case report: Apatinib combined with neoadjuvant therapy for primary squamous cell carcinoma of the breast: a case report - Gao, Fangfang; Li, Jingtai; Liao, Haoran; Fan, Pingming; Wang, Minjian; Liu, Yu; Ding, Linwei; Du, Guankui (Frontiers in Pharmacology, 2023)
Primary squamous cell carcinoma of the breast is a rare subtype of carcinoma of chemosis for which there is no effective chemotherapy regimen. Breast squamous cell carcinoma is usually “triple negative”, with poor chemotherapy effects and poor prognosis. Here, we report a successful case of primary breast squamous cell carcinoma treated with apatinib. The patient was treated with 2 cycles of apatinib. The efficacy was evaluated as partial remission, and a sublesion of approximately 4 cm fell off.